Analisis Proses Produksi Larva Udang Vanname (Litopenaeus Vannameii)Pada Penerapan Fungsi Manajemen di PT. Benur Top De Heus Askra Kendari - Rifqatul Jannah; Andi Baso Adil Natsir; Yusri Muhammad Yusuf (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Understanding and knowledge about the application of management functions needs to be studied to facilitate the success of seeding activities. This research was carried out for 6 months located at PT. Top De Heus Askra Kendari fry. The aim of this research is to find out how the production process flows in the application of management functions in vannamei shrimp (Litopenaeus vannameii) hatchery activities at PT. Top De Heus Askra fry. The type of research used is qualitative descriptive research. The data sources used come from primary data and secondary data with the research methods used namely the listening method and skill method, while the techniques used are recording and note-taking techniques, and the analysis tool uses PESTEL analysis. The research results show that the production process flow is interrelated with the management function in vannamei shrimp hatchery activities so that goals can be achieved. At PT. Benur Top De Heus Askra's planning function includes preparation of suggestions and maintenance infrastructure as well as installation and management of the aeration system and the organizing function consists of dividing employee duties and responsibilities, directing, namely carrying out the duties and responsibilities of each employee, and supervision, namely evaluating each activity. The hatchery production process flow activities start from managing the aeration system, preparing brood rearing tanks, receiving broodstock, feeding, spawning broodstock, hatching eggs, preparing larval rearing tanks, stocking naupli, managing water quality, feeding and harvesting.